2019
DOI: 10.1039/c9ra04905c
|View full text |Cite
|
Sign up to set email alerts
|

Removal of refractory organics in dinitrodiazophenol industrial wastewater by an ultraviolet-coupled Fenton process

Abstract: A significant amount of biorefractory organic wastewater is generated during the production of dinitrodiazophenol (DDNP). In this study, ultraviolet light (254 nm) that was coupled with the Fenton (UV-Fenton) process was applied to treat refractory organics in DDNP industrial wastewater. The effects of key parameters (i.e., H 2 O 2 dose, Fe 2+ dosage, and initial pH) on the treatment efficacy for DDNP industrial wastewater by the UV-Fenton process was investigated systematically. Alcohol quenching experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Dyes, as the prevalent organic contaminant in wastewater, are widely used in coloring and printing activities in paper, textile, leather, and cosmetic industries. [1][2][3][4] Dyecontaining wastewater can directly destroy the ecological balance of a water body and negatively affect human health. 5,6 It has been found that dyes are difficult to degrade by traditional biological methods owing to their complex structure with high molecular weight and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Dyes, as the prevalent organic contaminant in wastewater, are widely used in coloring and printing activities in paper, textile, leather, and cosmetic industries. [1][2][3][4] Dyecontaining wastewater can directly destroy the ecological balance of a water body and negatively affect human health. 5,6 It has been found that dyes are difficult to degrade by traditional biological methods owing to their complex structure with high molecular weight and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…UV–vis spectroscopy can characterize the aromaticity and relative contents of characteristic organics and is widely applied to analyze the changes in the typical structure of aromatic organics in leachate (Ran & Li, 2019). Figure 3 shows the UV–vis spectra of the MBR effluent before and after treatment with the UV, nFe 0 , H 2 O 2 , UV/nFe 0 , nFe 0 /H 2 O 2 , UV/H 2 O 2 , and UV/nFe 0 /H 2 O 2 systems.…”
Section: Resultsmentioning
confidence: 99%
“…At the UV/Fenton process, H2O2 is catalysed by Fe 2+ producing more OH radicals. Simultaneously, Fe 3+ can be transformed to Fe 2+ by UV, to catalyse H2O2, [15]. The main advantages of Fenton and UV/Fenton processes are the high reaction rate, the high efficiency in degrading pollutants, and mineralizing landfill leachates, [1].…”
Section: Introductionmentioning
confidence: 99%